Analisa Perencanaan Berbasis SNPT terhadap Penerapan Performance Based Planning - Priyo Sulistiyono, Tato (JURNAL ILMIAH GEMA PERENCANA, 2023)
This paper intends to investigate the financial planning policy based on university national standards in UIN Raden Mas Said Surakarta this study implements qualitative—data collected from documents related to planning based on university national standards in UIN Raden Mas Said Surakarta. The result shows that planning policy based on university national standards in UIN Raden Mas Said based are financial planning by involving quality assurance institutions and internal surveillance institutions. The University quality assurance body is the institution responsible for accreditation of the university and department. University internal surveillance is the institution that is responsible for conducting and controlling the financial budgeting. All of them collaborate with the financial planning body in UIN Raden Mas Said Surakarta